Validation of an ERAS protocol in gynecological surgery: interim analysis of an italian randomized controlled trial. (1st November 2019) - Ferrari, F; Forte, S; Sbalzer, N; Mauri, M; Zizioli, V; Sartori, E; Odicino, F
Abstract : Introduction/Background: Enhanced Recovery After Surgery (ERAS) is a new emerging standard of perioperative care for gynecological surgery. The aim of the study is to compare outcomes of conventional perioperative care with those of an ERAS protocol in women undergoing major gynecological surgery. Methodology: In this trial (clinicaltrials.gov NCT03347409 ), involving patients affected by benign gynecological pathology, endometrial or ovarian cancer, we randomly assigned patients to undergo conventional perioperative care (Standard) or ERAS protocol. The primary outcome was the length of hospitalization (LOH) in days with noninferiority claimed if the lower boundary of the two-sided 95% confidence interval of the between-group difference (Standard versus ERAS) was equal or greater than 1.5 days. Secondary outcomes include comparison of postoperative pain, vomiting and nausea, anesthesiological and surgical complications up to thirty days after surgery and the time-to-event in hours for bowel movements, flatus, drink, hunger, eating and walking and quality of recovery using a validated questionnaire. We further evaluated compliance to ERAS protocol. Results: We enrolled 138 patients and of them 70 (51%) underwent Standard protocol while 68 (49%) were assigned to ERAS. The two groups were similar with respect to age, BMI, Charlson-comorbidity-index, anesthesiological risk, smoking habits, surgical access and complexity of surgical procedures. Fifty-two patients (38%) underwent hysterectomy for benign surgery, 44 (32%) for endometrial cancer and 42 (30%) for ovarian cancer. LOH was 3.5 days shorter in ERAS protocol (CI95% 2.1–4.2; p=0.00). Subgroup analysis showed a greater advantage in patients underwent laparotomic surgery with a LOH 4.1 days shorter (CI95% 3.6–4.7; p=0.00), while for laparoscopic surgery LOH was 2.1 days shorter (CI95% 1.6–3.2; p=0.00). Secondary outcomes and update of the aforementioned data should be assessed yet. Conclusion: Application of ERAS protocol in gynecological surgery translated in a shorter LOH, regardless surgical access and pathology. Disclosure: Nothing to disclose.